Advances in 3D printing technology for preparing bone tissue engineering scaffolds from biodegradable materials - Wang, Zhen; Sun, Yanan; Li, Chen (Frontiers in Bioengineering and Biotechnology, 2024)
Bone tissue engineering (BTE) offers an effective repair solution by promoting bone tissue regeneration through the implantation of osteogenic cells or stem cells into biocompatible and biodegradable scaffolds. 3D bioprinting technology, using computer-generated 3D models as "blueprints" and assembling specialized "bio-inks," has been widely applied in the fabrication of tissue engineering scaffolds. This paper reviews the characteristics of scaffold materials for bone tissue engineering and compares the advantages and disadvantages of various materials used in 3D printing.Bioceramics exhibit excellent biocompatibility but are highly brittle; metal materials offer high strength but may trigger chronic inflammation; natural polymers have superior biocompatibility but poor mechanical properties; and synthetic polymers are highly tunable but may produce acidic byproducts during degradation. The paper summarizes recent applications of 3D bioprinting in bone tissue engineering, exploring the potential of combining 3D bioprinting technology with composite materials to enhance scaffold biocompatibility and mechanical performance. This opens new technological pathways for the personalized design of scaffolds in clinical applications. The study provides a unique perspective and theoretical support for advancing 3D bioprinting technology in bone regeneration and looks ahead to future developments in bone tissue engineering materials and 3D bioprinting.